Future Pedagogy Teachers Readiness Formation in Dual-Oriented Education - Elmira, Aitenova; Leskul, Ibraimova; Alua, Smanova; Malik, Sultanbek; Zhambyl, Beknazarov; Laura, Shalabayeva (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The socio-economic development of society puts forward new requirements for the teacher of training: he must be competent, educated, informed, have developed thinking. The professionalism of future teachers of training is of priority importance, and its formation is a necessary condition for the intensification of education. The scientific search for a solution to the problem of the formation of professionalism among future teachers of training is aimed at resolving the contradictions between: - the need of society for training specialists with a high level of professionalism and an insufficient level of their professional training; the need for personnel with a high> level of professionalism, and the undeveloped process of forming the professionalism of teachers of training at a university; the practical need for the purposeful development of the professionalism of future teachers and the existing conditions for organizing their professional development in an engineering and pedagogical university; the expediency of creating a developmental space and the existing traditional approach to the development of professionalism among future teachers of training at a university. This research aims to analyze future pedagogy teachers’ readiness formation in dual-oriented education. It is possible to resolve these contradictions based on scientific support for the integration process of development and formation of the personality of the future teacher. With regard to the topic of the research, we are talking about rethinking the goals and social essence of the training process. In this paper, we have analyzed the training programmes offered to the teachers, surveying the effects and benefits of professional advancement on creating new knowledge and improving the quality of teaching. The survey results have verified the main hypothesis regarding the effect of professional readiness development in raising the quality of teaching, but they have not verified a completely auxiliary hypothesis that views (considers) as a mechanism to meet the professional development needs of teachers.